2021
DOI: 10.3389/fbioe.2021.691450
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rotator Cuff Deficiencies on Muscle Forces and Glenohumeral Contact Force After Anatomic Total Shoulder Arthroplasty Using Musculoskeletal Multibody Dynamics Simulation

Abstract: Anatomic total shoulder arthroplasty (ATSA) is widely used to treat the diseases of the glenohumeral (GH) joint. However, the incidence of rotator cuff tears after ATSA increases during follow-up. The effects of rotator cuff deficiencies after ATSA on the biomechanics of the GH joint are to be investigated. In this study, a musculoskeletal multibody dynamics model of ATSA was established using a force-dependent kinematics (FDK) method. The biomechanical effects were predicted during arm abduction under differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…This study is the first to use a validated anatomical shoulder model to develop a 6-DOF musculoskeletal shoulder model of RSA, allowing three translations of the glenohumeral joint. As this study demonstrated that the maximum RMSE (0.18 BW) and minimum correlation coefficient ( r = 0.740) are within the reported range of RMSEs (0.12–0.28 BW) and correlation coefficients (0.701–0.962) of previous studies ( Chen et al, 2021 ; Ro et al, 2022 ), the 6-DOF musculoskeletal shoulder model of RSA proposed herein appears to predict JCFs during abduction sufficiently.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This study is the first to use a validated anatomical shoulder model to develop a 6-DOF musculoskeletal shoulder model of RSA, allowing three translations of the glenohumeral joint. As this study demonstrated that the maximum RMSE (0.18 BW) and minimum correlation coefficient ( r = 0.740) are within the reported range of RMSEs (0.12–0.28 BW) and correlation coefficients (0.701–0.962) of previous studies ( Chen et al, 2021 ; Ro et al, 2022 ), the 6-DOF musculoskeletal shoulder model of RSA proposed herein appears to predict JCFs during abduction sufficiently.…”
Section: Discussionsupporting
confidence: 85%
“…Quantitative assessments of the 6-DOF anatomical shoulder model were performed by evaluating the root-mean-squared error (RMSE) and Pearson’s correlation coefficient ( r ) compared to the human in vivo JCFs from 10° to 90° abduction ( Bergmann et al, 2011 ) and compared to previously predicted JCFs from 13° to 109° abduction ( Quental et al, 2016 ). Because of the lack of previously reported RMSEs and correlation coefficients corresponding to the intact glenohumeral JCFs, the calculated RMSEs and correlation coefficients were indirectly evaluated by comparing them with the previously reported values in the 6-DOF musculoskeletal model of total joint arthroplasty ( Chen et al, 2021 ; Ro et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…This added load can cause the humeral head to move superomedially, resulting in potential impingement and harm to implant surfaces. In a biomechanical study, Chen et al 12 investigated the effects of RCTs after TSA on muscle forces and glenohumeral contact force during arm abduction. Their findings revealed that subscapularis deficiency increased the maximum deltoid force by 36%, whereas combined infraspinatus, supraspinatus, subscapularis, and teres minor deficiencies led to a 53% increase.…”
Section: Implications Of Cuff Deficiency On Postoperative Biomechanic...mentioning
confidence: 99%
“…After TSA, RCTs have been shown to affect joint dynamics, resulting in inferior functional outcomes and an increased incidence of complications when compared to patients with intact rotator cuffs 6,12 .…”
Section: Implications Of Cuff Deficiency On Postoperative Biomechanic...mentioning
confidence: 99%
“… 25 , 27 The results of arthroscopic rotator cuff repairs are generally favorable; however, numerous documented factors, including age, magnitude of cuff tear, number of torn tendons, degree of atrophy, workers compensation status, and delayed time to repair, place the patient at high risk of treatment failure. 1 , 8 , 10 , 39 …”
mentioning
confidence: 99%